The Value of Liver Transplantation for Methylmalonic Acidemia - Yi-Zhou Jiang (Frontiers in Pediatrics, 2019)
Introduction: MMA is a rare autosomal recessive disorder with the manifestation of recurrent and severe episodes of acute metabolic decompensation or a variety of long-term complications that require timely treatment. While conventional long-term medical and dietary management cannot prevent rapid progression of conditions in patients with severe complications, LT, or CKLT has become an option.Methods: We reviewed the literature for MMA patients undergoing LT/CKLT published since 2006, and data on metabolic decompensation status, protein dietary, neurological damage, renal insufficiency, and developmental delay before and after transplantations were compared to evaluate the clinical value of the procedure in the treatment of MMA.Results: To date, some successful LTs/CKLT procedures have prolonged survival and resulted in better quality of life in patients (lowered urine/plasma MMA levels but still much higher than normal, reduced onset of metabolic stroke, occasional improved developmental delay, and relaxed protein diet), although these procedures cannot reverse neurological damage or thoroughly stop the progress of complications, such as renal dysfunction.Conclusion: LT is the only effective treatment for MMA patients with recurrent metabolic decompensation. However, it is still possible that neurological and renal damage remains irreversible. Metabolism-correcting medications should be administered even after surgery.